Drilling of 7075 aluminum alloys - Dahnel, Aishah Najiah; Naiman, Mohamad Noor Ikhwan; Mohd Farid, Muhammad Azim Mirza; Abdul Rahman, Ahmad Faris; Meera Mydin, Nur Munirah (Intech Open, 2022)
Aluminum alloy (Al 7075) has been increasingly used as structural components in automotive and aerospace industry due to their low density, high strength and good corrosion resistance compared with other metals. To manufacture and assemble the components, drilling operations are often conducted. However, Al 7075 is ductile and soft, which causes difficulty in drilling, resulting in material adhesion, high tool wear, short tool life and poor hole quality. As a result of the poor hole quality, there is a high percentage of part rejection, which can increase the manufacturing time and cost. This chapter discusses challenges and techniques to drill Al 7075 in terms of the cutting parameters and drilling conditions to prolong the tool life and achieve good hole quality. Drilling experiments on Al 7075-T6 (heat-treated) were conducted using carbide cutting tools at various cutting parameters. Reducing cutting speed and increasing feed rate resulted in reducing tool wear, whereas a reduction in surface roughness, hence improved machined surface finish, was found when both cutting speed and feed rate were reduced in drilling Al 7075-T6. Producing good hole quality is vital during the drilling process to ensure a good assembly and product service performance.